expand x^2-6x+9 = 5
or x^2-6x+4 =0
2006-11-15 15:07:13
·
answer #1
·
answered by Mein Hoon Na 7
·
0⤊
0⤋
Say we've 0 = x^2 + 2xy + y To ingredient, only write out 2 contraptions of parenthesis: ( )( ) ascertain the signs and indicators in the midsection: (if the 0.33 variety in the equation is beneficial, the signs and indicators are the two beneficial or the two adverse. if it relatively is adverse, then a million pos. a million neg.) ( + )( + ) What 2 numbers' product equals the 1st variety and may be used to ascertain the 2d variety: (x + )(x + ) What 2 numbers equals the 0.33? (x + y)(x + y) you're executed! If we had x^2 + 6x - 7 = 0 to end the sq.: a million. upload the non variable coefficient to the choice component: x^2 + 6x = 7 2. ingredient out the 'a' term a million(x^2 + 6x) = 7 3. Take a million/2 b, then sq. it and upload it to the two sides a million/2(6) = 3 (x^2 + 6x + (3)^2) = 7 + (3)^2 4. ingredient the quadratic you get and simplify the main appropriate component (x + 3)^2 = sixteen 5. Now, we've 'p' form of a quadratic: (x + 3)^2 = (y + sixteen) The vertex is (-3,-sixteen) 6. resolve for x to get the roots x + 3 = +/- 4 x = -7 x = a million 7. replace x back in to get the y int (to envision, the y int is often the 0.33 term in a quadratic equation) for that reason it relatively is -7 8. There you pass. you have the vertex, axis of sym (while you're graphing up/down parabolas, it relatively is the y term; while you're graphing left/suitable parabolas, it relatively is the x term) the y int/(x int in sideways parabolas) and roots.
2016-10-15 14:53:28
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
It is x^2-6x+4=0.
2006-11-15 15:15:41
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
x^2 - 6x + 4 = 0
2006-11-15 15:09:26
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
yes, this is a quadratic....heres how you go about this problem
you are given (x-3)^2=5
start by foiling the left
(x-3)(x-3)
so you now have
x^2-3x-3x+9=5
or
x^2-6x+9=5
so now you want to move the 5 to the left side because remember we need our equation set equal to zero...to do this subtract 5 from both sides
so you now have
x^2-6x+9-5=0
and your final answer is
x^2-6x+4=0
(here a=1, b=-6, c=4)
hope this helps
matttlocke
2006-11-15 15:12:17
·
answer #5
·
answered by matttlocke 4
·
0⤊
0⤋
x^2-6x+9=5
adding -5
x^2-6x+4=0
2006-11-15 15:09:30
·
answer #6
·
answered by raj 7
·
0⤊
0⤋
(x-3)^2 = 5
x^2-6x+9=5
x^2-6x-4=0
2006-11-15 15:08:43
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋